2021
DOI: 10.7759/cureus.16216
|View full text |Cite
|
Sign up to set email alerts
|

Potential Predictors and Prevalence of Helicobacter pylori Infection Among Adult Patients With Dyspepsia: A Retrospective Study From Qatar

Abstract: To study the prevalence of Helicobacter pylori (H. pylori) infection among dyspeptic patients of various ethnic origins in Qatar and determine the association between H. pylori infection and various demographic factors and endoscopic findings. MethodsA retrospective data review was carried at Alkhor Hospital, Hamad Medical Corporation, Qatar. Adult patients who underwent endoscopy for the evaluation of dyspepsia between January 2011 to December 2017 were included. Patients who underwent endoscopy for reasons o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Therefore, the recent prevalence of H. pylori among dyspeptic patients in the country seems to be similar. In other Asian and African countries, a similar prevalence of H. pylori was described, e.g., 40.9% (the CLO test) in Qatar [ 29 ], 36% (histology) in Uganda [ 30 ], and 31.2% (histology, the RUT, and culture) in Iran [ 31 ]. Nevertheless, the notably high detection rate of H. pylori (PCR and the CLO test) (67%) was shown in a study in southern Bangladesh (Chittagong) [ 32 ], suggesting the presence of highly endemic areas within the country.…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, the recent prevalence of H. pylori among dyspeptic patients in the country seems to be similar. In other Asian and African countries, a similar prevalence of H. pylori was described, e.g., 40.9% (the CLO test) in Qatar [ 29 ], 36% (histology) in Uganda [ 30 ], and 31.2% (histology, the RUT, and culture) in Iran [ 31 ]. Nevertheless, the notably high detection rate of H. pylori (PCR and the CLO test) (67%) was shown in a study in southern Bangladesh (Chittagong) [ 32 ], suggesting the presence of highly endemic areas within the country.…”
Section: Discussionmentioning
confidence: 69%
“…In the study of Aminde JA et 2 reported that the average age of the participants was 40.7 ± 19.1 years with age range of 7 to 96 years and out of all 452 cases females were in majority 63.6%. In the retrospective Study of Naushad VA et al 11 from Qatar found inconsistent findings regarding gender as out of all 638 cases males were 58.8%, while consistently mean age was 42.2 years with age range of 18 to 79 years. The variation in the average age and gender between this In this study as per clinical presentation 78.6% patients had epigastrium pain, 36.7% had flatulence, 67.1% had belching, 40.0 had nausea, 12.4% had vomiting, 80.5% had bloating and 81.9% had burning.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, Kouitcheu Mabeku LB et al 10 demonstrated that as per clinical signs and symptoms the epigastric pain and burning and recurrent burping were the commonest among all the cases (100%) followed by Flatulence/ bloating was in 70.45% cases and Nausea/Vomiting in 34.1% of the cases. Despite the fact that the study of Naushad VA et al 11 from Qatar reported that the commonest symptom was epigastrium pain 80.6% followed by belching 8.8%, nausea 10.2%, vomiting 9.6%, heart burn 26.2% and melena 6%.…”
Section: Discussionmentioning
confidence: 92%